Mandatory CSR expenditure and firm performance in lag periods: Evidence from India - Kofi Mintah Oware (Cogent Business & Management, 2022)
This study examines whether mandatory CSR expenditure has the same effect on firm performance after years of implementation. The data set consists of 80 firms with 640 firm-year observations on the Bombay Stock Exchange in India from 2013 to 2020 that practised sustainability reporting. This study used panel regression with random effect & fixed effect, and generalized method of moments (GMM) assumptions. The first findings show that mandatory CSR expenditure in the current year negatively affects Tobin q. The second findings show that mandatory CSR expenditure in the lag years (1 to 2~years) has no association with return on assets or Tobin q. The third findings show that mandatory CSR expenditure in the lag years (3 and above) has no association with return on assets or Tobin q. The re-alignment between voluntary CSR investment and associated benefit mostly happens in lag 1 and 2, but mandatory CSR shows insignificant results. Our results are robust to controlling firm-level variables. Previous studies examined mandatory CSR expenditure on firm performance, but this new study addresses the shorter and longer lag of mandatory CSR expenditure on firm performance. The study's implication suggests the possible acceptability of allowing firms to write CSR expenditure as tax-deductible until the CSR expenditure and the associated benefit are aligned. However, until then, managers must be authorised to spend on CSR activities, knowing there is a safety net when CSR expenditures do not produce positive firm performance in subsequent years.
Keywords: 650; Firm performance; India; Institutional theory; Lag effect; Mandatory CSR expenditure